Efficient ab initio plus analytic calculation of the effect of GaN layer tensile strain in AlGaN/GaN heterostructures. (27th August 2019) - Date, Mihir; Mukherjee, Sudipta; Ghosh, Joydeep; Saha, Dipankar; Ganguly, Swaroop; Laha, Apurba; Ghosh, Prasenjit
Abstract: We have addressed the existing ambiguity regarding the effect of tensile strain in the underlying GaN layer on Al x Ga1− x N/GaN heterostructure properties. The bandgaps and band-offsets for Al x Ga1− x N on strained GaN were first computed using density functional theory (DFT), in the generalized gradient approximations (GGA) and hybrid functional Gaussian–Perdew–Burke–Ernzerhof (Gau–PBE) regimes. We propose a simple model to relate the GGA and Gau–PBE bandgaps, which is used to determine the realistic bandgaps of strained AlGaN. The bandgaps and band-offsets from the DFT calculations are then used to analytically calculate the two-dimensional electron gas density in an Al x Ga1− x N/GaN hetero-interface. Our bandstructure calculations show that it is not possible to induce significant change in band-offsets through strain in the GaN layer. The charge-density calculations indicate that such strain can, however, modulate the polarization charge and thereby enhance the 2DEG density at the AlGaN/GaN interface substantially.